Negative photoperiod induces an increase in the number of ovulations in dairy cattle - Fernando LÓPEZ-GATIUS (The Society for Reproduction and Development, 2023)
This study sought to examine the impact of negative photoperiod on the incidence of multiple ovulations and pregnancies in dairy cattle. The study population consisted of 5,373 pregnant cows in their third or greater lactation that experienced their first post-partum pregnancy after spontaneous estrus. The positive photoperiod (increasing day-length) extends from December 22 to June 21, whereas the negative photoperiod (decreasing day-length) extends from June 22 to December 21. The odds ratios (ORs) for multiple ovulations and pregnancies in cows that became pregnant during the negative photoperiod and the remaining cows that became pregnant during the positive photoperiod were 1.4 and 1.3 (P < 0.0001), respectively. The ORs for cows that became pregnant ≥ 90 days in milk and the remaining cows that became pregnant < 90 days in milk were 4.3 and 4.1 (P < 0.0001), respectively. No significant differences were detected in the monthly rates of multiple ovulations or pregnancies during positive and negative photoperiods. Thus, the present study demonstrates that the ovarian function in cows is related to changes in day-length, with decreasing day-length being associated with greater multiple ovulation and pregnancy rates. The present study also shows that positive and negative photoperiods exhibit different trends. The results of this study are consistent with a growing body of work demonstrating the effects of photoperiod patterns on the reproductive physiology of cows, with clear implications for twin pregnancy prevention.